The beekeeper's daughter [large type] - Montefiore, Santa, 1970- (Thorndike Press, 2015)
England, 1932: Grace Hamblin is growing up in a rural idyll. The beekeeper's daughter, she knows her place and her future -- that is until her father dies and leaves her alone. Alone, that is, except for one man who she just can't shake from her thoughts... Massachusetts, 1973: Grace's daughter Trixie Valentine is in love with an unsuitable boy. He's wild and romantic, and in a band that might be going somewhere. But when tragedy strikes and he has to go home to England, he promises to come back to Trixie one day, if only she will wait for him. Both mother and daughter are searching for love and happiness, unaware of the secrets that bind them. To find what they are longing for they must confront the secrets of the past, and unravel the lies told long ago.